2015
DOI: 10.1007/s10933-015-9870-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish stocking on mountain lake plankton communities identified using palaeobiological analyses of bottom sediment cores

Abstract: The artificial introduction of fish into a naturally fishless lake can effectively modify the food web and trophic status of that lake. We observed changes in the zooplankton community after stocking fish in Przedni Staw Polski, an oligotrophic mountain lake in the Tatra Mountains (Poland). Results were compared with observations about a stocked lake that naturally contained fish (Morskie Oko), and with two fishless lakes that served as reference sites. The main change observed in the cladoceran community of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…Outside Finland, R. latens fossils have been recorded from oligotrophic lakes in alpine regions of central and eastern Europe (Fig. 1; Van Damme & Nevalainen, 2019); in the Swiss Alps (two lakes, Bigler et al, 2006), northern Italy (Lake Ledro, Milan et al, 2017) and Tatra mountains in Poland (two lakes, Sienkiewicz & Gąsiorowski, 2016). Recently, Sweetman & Sarmaja-Korjonen (2017) found R. latens fossil remains, corresponding to those from Finland, from two lakes in the Canadian Arctic treeline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside Finland, R. latens fossils have been recorded from oligotrophic lakes in alpine regions of central and eastern Europe (Fig. 1; Van Damme & Nevalainen, 2019); in the Swiss Alps (two lakes, Bigler et al, 2006), northern Italy (Lake Ledro, Milan et al, 2017) and Tatra mountains in Poland (two lakes, Sienkiewicz & Gąsiorowski, 2016). Recently, Sweetman & Sarmaja-Korjonen (2017) found R. latens fossil remains, corresponding to those from Finland, from two lakes in the Canadian Arctic treeline.…”
Section: Discussionmentioning
confidence: 99%
“…The taxon's Holocene and current affiliation to dystrophic and oligotrophic sites (e.g. Bigler et al, 2006;Nevalainen, 2008;Sienkiewicz & Gąsiorowski, 2016;Nevalainen et al, 2018;Van Damme & Nevalainen, 2019) indicates its preference to limno-climatic and habitat conditions resembling periglacial environments, including semiaquatic wetlands, shallow and lush lake littorals and clear and cold waters. R. latens has clearly a low temperature preference, as it is associated with cold temperatures across Finland (Nevalainen et al, 2013) and also in the north boreal-subarctic transition zone of northern Finnish Lapland (Nevalainen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Введение аллохтонных видов рыб часто оказывает более сильное воздействие на зоопланктон, чем другие факторы [46]. Неоднократное вселение Onchorynchus mykiss [33] и арктического гольца Salvelinus alpinus (Linnaeus, 1758) [30] привело к существенному изменению в зоопланктоне горных альпийских озер.…”
Section: материал и методикиunclassified
“…Железо, находясь в повышенных концентрациях, действовало в противоположном направлении и стимулировало укрупнение особей в сообществах. Полученные авторами результаты подтверждают чувствительность горных холодноводных озер к внешним воздействиям, что подчеркивалось и другими исследователями [30,33,34,46].…”
Section: материал и методикиunclassified
“…In Poland, subfossil Cladocera were analysed mainly in lakes with higher trophic status, from mesotrophic to hypertrophic, while studies on sediments from deep oligotrophic mountain lakes revealed a practically complete absence of species belonging to the Bosminidae family. Oligotrophic lakes in the Tatra Mountains (Szeroczyńska, 2006;Sienkiewicz and Gąsiorowski, 2016), probably had such a low availability of nutrients during the whole Holocene, that edaphic conditions were almost never suitable for the Bosminidae existence. B. longirostris was found only in the sediment deposited during the modern time.…”
Section: Interestinglymentioning
confidence: 99%